ANALISIS WACANA KRITIS MODEL VAN DIJK DALAM PEMBERITAAN ATURAN PENGGUNAAN TOA MASJID DAN PERNYATAAN MENAG YAQUT MENGANALOGIKAN SUARA AZAN DENGAN GONGGONGAN ANJING DI MEDIA ONLINE TEMPO.COM - Pepi Supita; Agus Hamdani (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This study focuses on the coverage of Minister of Religious Affairs Yakut's statement regarding the call to prayer (azan) compared to the sound of barking dogs currently happening in Indonesia, as published in several online media outlets, particularly Tempo.com. While there are numerous other online media sources producing news related to this issue, the researcher attempts to analyze these two specific online media outlets. The aim of this study is to describe the critical discourse analysis of the